2011
DOI: 10.1007/s00426-011-0324-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of response conflict on voluntary task switching: a novel test of the conflict monitoring model

Abstract: The conflict monitoring model of cognitive control posits that response conflict triggers a top-down enhancement of a task's representation in working memory. In the present study, we conducted a novel test of the conflict monitoring model using a voluntary task switching paradigm. We predicted that a task's representation would be enhanced following events associated with high response conflict (i.e., incongruent trials and incorrect responses), leading participants to voluntarily choose to repeat that task m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
4

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 38 publications
6
36
4
Order By: Relevance
“…The main effect of agency was significant ( F (1,27) = 6.4, p < .05), as participants were faster to voluntarily choose the next task (767 ms) than they were to confirm processing of the explicit task cues (800 ms). In line with previous findings (Arrington & Logan, 2005; Orr et al, 2012; Orr & Weissman, 2011), participants were faster to choose to repeat tasks (778 ms) than to switch tasks (788 ms; F (1,27) = 4.9, p < .05). Further, there was a main effect of choice congruency ( F (1,27) = 7.7, p = .001).…”
Section: Resultssupporting
confidence: 91%
“…The main effect of agency was significant ( F (1,27) = 6.4, p < .05), as participants were faster to voluntarily choose the next task (767 ms) than they were to confirm processing of the explicit task cues (800 ms). In line with previous findings (Arrington & Logan, 2005; Orr et al, 2012; Orr & Weissman, 2011), participants were faster to choose to repeat tasks (778 ms) than to switch tasks (788 ms; F (1,27) = 4.9, p < .05). Further, there was a main effect of choice congruency ( F (1,27) = 7.7, p = .001).…”
Section: Resultssupporting
confidence: 91%
“…Intuitively one would think that free choices are mostly determined by our own intentions and internal goals. Previous research, however, suggests that free choices may not be as free as they seem to be, and are strongly influenced by cues from the environment or past experiences (Bargh et al, 2001;Arrington & Logan, 2005;Arrington, Weaver & Pauker, 2010;Wenke, Fleming & Haggard, 2010;Orr & Weissman, 2011;Orr, Carp, & Weissman, 2012;Demanet et al, 2013;Orr & Banich, 2014). Wenke and colleagues (2010), for example, found that subliminal primes influence the responses on free choice trials in such a way that people responded significantly more slowly when they chose to act against the prime (in a prime-incompatible way).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In these studies, the focus is generally on measures of task choice rather than performance and they address questions related to why subjects select to perform a given task on the current trial when it is not uniquely specified by the characteristics of the experimental environment. Task choice is influenced by many factors including preparation time (Arrington & Logan, 2005), concurrent working memory load (Demanet, Verbruggen, Liefooghe, & Vandierendonck, 2010; Weaver & Arrington, 2010; Weywadt & Butler, 2013), stimulus repetition (Mayr & Bell, 2006), task difficulty (Liefooghe, Demanet, & Vandierendonck, 2010; Orr, Carp, & Weismann, 2011; Yeung, 2010), and individual differences in executive control (Arrington & Yates, 2009). Looking across these various studies, it is apparent that task choice involves both internally- and externally-driven processes.…”
mentioning
confidence: 99%